Controlling the propagation asymmetry of hyperbolic shear polaritons in beta-gallium oxide - Joseph Matson; Sören Wasserroth; Xiang Ni; Maximilian Obst; Katja Diaz-Granados; Giulia Carini; Enrico Maria Renzi; Emanuele Galiffi; Thomas G. Folland; Lukas M. Eng; J. Michael Klopf; Stefan Mastel; et al. (Nature Communications, 2023)
Abstract Structural anisotropy in crystals is crucial for controlling light propagation, particularly in the infrared spectral regime where optical frequencies overlap with crystalline lattice resonances, enabling light-matter coupled quasiparticles called phonon polaritons (PhPs). Exploring PhPs in anisotropic materials like hBN and MoO3 has led to advancements in light confinement and manipulation. In a recent study, PhPs in the monoclinic crystal β-Ga2O3 (bGO) were shown to exhibit strongly asymmetric propagation with a frequency dispersive optical axis. Here, using scanning near-field optical microscopy (s-SNOM), we directly image the symmetry-broken propagation of hyperbolic shear polaritons in bGO. Further, we demonstrate the control and enhancement of shear-induced propagation asymmetry by varying the incident laser orientation and polariton momentum using different sizes of nano-antennas. Finally, we observe significant rotation of the hyperbola axis by changing the frequency of incident light. Our findings lay the groundwork for the widespread utilization and implementation of polaritons in low-symmetry crystals.